Coating composition for reinforced protective layer

JP7639242B2Active Publication Date: 2025-03-04AKZO NOBEL COATINGS INT BV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024541658
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-17
Filing Date
2023-01-17
Publication Date
2025-03-04
Estimated Expiration
2043-01-17

Smart Images

  • Figure 0007639242000012
    Figure 0007639242000012
  • Figure 0007639242000013
    Figure 0007639242000013
  • Figure 0007639242000001
    Figure 0007639242000001
Patent Text Reader

Abstract

The present invention relates to a coating composition comprising a resin system comprising an organic film-forming resin and, optionally, a curing agent reactive with the organic film-forming resin, a lithium salt having a solubility in water ranging from 0.01 to 120 g / L at 20° C. selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate, and a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), the zinc salt of DMTD being present as solid particles, the surface of which is at least partially covered by a layer of a film-forming polymer. The zinc salt of DMTD has been shown to have a synergistic effect on enhancing the barrier properties of the protective layer formed at coating defects due to the presence of the lithium salt. Furthermore, the coating composition has an improved pot life.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the use of coating compositions having protective properties, particularly useful for metal substrates. [Background technology]

[0002] Protective coatings are widely used to protect substrates, especially metal substrates, from corrosion. Hexavalent chromium compounds have long been used as corrosion inhibitors in protective coatings and conversion treatments of metal surfaces. However, hexavalent chromium is toxic and is therefore scheduled to be phased out for environmental, worker safety, and regulatory reasons. Although alternative chromium-free inhibitors have been proposed in recent years, many formulations struggle to meet the corrosion resistance standards, especially in industry.

[0003] Although much progress has been made in chromium substitution in corrosion protection coatings, it remains desirable to provide Cr-free coatings that have improved long-term corrosion resistance properties that are equivalent to or better than conventional Cr-containing coatings.

[0004] Recently, coating compositions with lithium salts have been proposed as an alternative to Cr-containing coatings. See, for example, "Chemical Properties of Coatings with Lithium Salts," IEEE Transactions on Materials Science and Engineering, Vol. 13, No. 1, pp. 1171-1175, 2002. As described in this paper, coating compositions with lithium salts have been demonstrated to have anticorrosive activity due to the formation of a protective layer on the substrate metal at locations where the coating deposited from the coating composition with lithium salt has defects. Such a layer was found to contain aluminum, oxygen and lithium that have leached from the coating. The protective layer provides a barrier between the metal surface at the coating defect and the corrosive environment. This barrier function and the strength of this protective layer may be important for long-term protection. Insufficient barrier function or low strength of the formed protective layer may result in localized metal defects and corrosion.

[0005] It would be desirable to provide coating compositions that have improved barrier properties. It would further be desirable to provide coating compositions that have improved pot life and minimal side reactions that occur during open time. [Prior art documents] [Non-patent literature]

[0006] Visser, P., Liu, Y., Terryn, H. et al. “Lithium salts as leachable corrosion inhibitors and potential replacement for hexavalent chromium in organic coatings for the protection of aluminum alloys” J Coat Technol Res 13, 557-566 (2016) Summary of the Invention

[0007] The inventors have found that when the coating composition also contains a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), the protective layer formed on the coating defects by the action of the lithium salt exhibits a significantly higher barrier function, as observed by electrochemical impedance spectroscopy (EIS). The zinc salt of DMTD acts as an enhancer of the barrier function of the protective layer formed on the exposed metal surface. However, when the zinc salt of DMTD is used in the coating composition, its activity may be reduced due to reactivity with the coating components, such as epoxy resins, which may also have a negative effect on the pot life of the coating composition.

[0008] In the present invention, the strengthening agent is provided in a surface-modified form that allows both to maintain its strengthening activity and to prevent its reaction with the coating components.

[0009] Thus, the present invention provides in a first aspect a method for producing a method for treating a cancer comprising the steps of: a) a resin system comprising an organic film-forming resin and, optionally, a curing agent reactive with the organic film-forming resin; b) a lithium salt having a solubility in water in the range of 0.01 to 120 g / L at 20° C. selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate; c) a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), the zinc salt of DMTD being 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII); Including, The zinc salt of DMTD is present as solid particles, the surface of which is at least partially covered by a layer of a film-forming polymer; A coating composition is provided.

[0010] In another aspect, the present invention provides a method of coating a metal substrate, comprising the steps of: a) applying a coating composition according to the present invention to a metal substrate; b) curing the applied coating composition; The present invention provides a method comprising:

[0011] In a further aspect, the present invention also provides a metal substrate coated with a coating composition according to the present invention. [Brief description of the drawings]

[0012] [Figure 1] 1 shows flow cup viscosity change with time after mixing for several embodiments of the present invention and comparative examples. [Diagram 2] 1 shows the flow cup viscosity change with time after mixing for a comparative coating composition and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Surprisingly, the inventors have found that the use of zinc salts of DMTD enhances the protective layer formed by lithium ions on the metal surface at coating defects when used with lithium salts selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate in the coating composition. The formation of a protective layer by lithium ions has previously been shown to be the mechanism of corrosion protection of lithium salts. When a coating defect forms in a cured coating, thus exposing the metal substrate and making it susceptible to corrosion, lithium ions leach from the coating to the metal surface and contribute to the formation of a protective layer at the surface. The presence of such a protective layer can be observed and its barrier properties quantified using electrochemical impedance spectroscopy (EIS). See, e.g., J. Appl. Phys. Lett. 2003, 143:1311-1320. This electrochemical method allows for the quantification of the barrier properties of the protective layer at the damaged area (scribe) created by the active protective mechanism (leaching) of the coating after exposure to accelerated corrosion tests (e.g., neutral salt spray exposure).

[0014] The magnitude of the barrier function is derived from the electrochemical impedance spectrum. The impedance modulus plot is the impedance modulus (Ω cm) as a function of frequency range (Hz). 2 ) The increase in impedance coefficient in the mid-frequency range 10 Hz can be related to the formation of a protective layer in the damaged area (scribe). The increase in impedance coefficient at low frequencies (10 mHz) can be related to the inhibition of corrosion processes at the substrate. An important advantage of using EIS is the ability to quantify differences between coating formulations that cannot be observed or quantified by visual methods.

[0015] However, the use of zinc salts of DMTD in coating compositions is tricky due to the active thiol groups of the DMTD molecule, which may be reactive towards other coating components. In the present invention, the toughening agent is provided in an encapsulated form (covered with a layer of film-forming polymer), which makes it possible both to maintain its toughening activity and to prevent its reaction with the coating components.

[0016] In the present invention, the zinc salt of DMTD is present as solid particles, the surface of which is at least partially covered by a layer of film-forming polymer.The surface can be partially or completely covered by the film-forming polymer layer, which can be observed, for example, by a microscope.Preferably, the surface is covered by at least 80%, more preferably at least 90%, even more preferably at least 95%, which can be estimated from a representative number of microscopic images.

[0017] References herein to a "film-forming polymer" refer to a polymer that has already formed a film (often referred to as "cured") and that no longer forms a film upon heating, drying, or contact with a curing agent.

[0018] The coating composition according to the invention is preferably chromium-free. "Chromium-free" means in particular free of Cr(VI) compounds, e.g. any Cr compound from chromates.

[0019] The coating composition according to the invention comprises a) a resin system comprising an organic film-forming resin and, optionally, a curing agent reactive with the organic film-forming resin. Within this specification, the term "film-forming resin" includes not only polymers but also monomers or oligomers that form a polymer system during curing of the coating. By organic film-forming resin is meant that the polymer, monomer or oligomer is organic (carbon-containing compound). The coating composition is preferably free of polysiloxanes. The coating composition is preferably not a sol-gel composition.

[0020] The film-forming resin may be selected, for example, from epoxy resins, hydroxy-functional resins (such as polyesters and poly(meth)acrylates), resins with one or more blocked hydroxyl groups (such as acetals), oxazolidine resins, carboxylic acid-functional resins), polyacrylates, polyurethanes, polyethers, polyaspartic esters, (blocked) isocyanates, thiol-functional resins, amine-functional resins, amide-functional resins, imide-functional resins (e.g., maleimides), alkyd resins, resins containing at least one olefinically unsaturated bond, silane-containing resins, polysiloxane resins, acetoacetate resins, functional (curable) fluorinated resins, and mixtures and hybrids thereof.

[0021] The present invention is particularly useful in embodiments in which the film-forming resin comprises an epoxy resin. Epoxy resins are epoxy-functional polymers with an epoxy equivalent weight greater than 1, typically about 2. The most commonly used epoxy resins are polyglycidyl ethers of cyclic polyols, such as bisphenol A, resorcinol, hydroquinone and catechol, or polyglycidyl ethers of polyols, such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-bis(hydroxymethyl)cyclohexane.

[0022] The film-forming resin is preferably present in the coating composition according to the invention in an amount of from 1 to 99% by weight, more preferably from 10 to 90% by weight, and even more preferably from 20 to 80% by weight, based on the total weight of the non-volatile components of the coating composition.

[0023] The coating composition may contain a curing agent reactive with the film-forming resin. The curing agent contains a functional group that is reactive with the functional group of the resin. The type of curing agent depends on the nature of the film-forming resin. The curing agent suitable for a particular film-forming resin is common knowledge to those skilled in the art.

[0024] The epoxy resin-containing composition preferably contains an aliphatic or aromatic amine hardener, a polyamide hardener, a thiol-based hardener. More preferably, the hardener comprises an amine-functional compound. Suitable epoxy resins are bisphenol A, bisphenol F, bisphenol A / F, novolac and aliphatic epoxy resins, such as Epikote 828 from Hexion Europe BV. Suitable amine hardeners are aliphatic amines and their adducts (e.g., Ancamine® 2021, Ancamine® 2500), phenalkamines, cycloaliphatic amines (e.g., Ancamine® 2196), amidoamines (e.g., Ancamide® 2426), polyamides and their adducts, and mixtures thereof. Melamine resins, preferably methylated melamine resins, such as hexamethoxymethylmelamine (HMMM), commercially available as Cymel® 350 from Allnex, are particularly preferred.

[0025] The epoxy / NH molar ratio in the epoxyamine-based coating composition is preferably in the range of 0.6-2.0, more preferably 0.8-1.7. For the solvent-based epoxyamine coating composition, the epoxy / NH molar ratio is preferably in the range of 0.6-1.4, more preferably 0.8-1.2, most preferably 0.85-1.1.

[0026] The coating composition may be a one-component or two-component (2K) composition, or a composition having three or more components. Preferably, the composition is a 2K composition. A 2K coating composition consists of two components that are stored separately and mixed immediately before application to a substrate. Typically, the first component contains an organic film-forming resin and the second component contains a hardener.

[0027] The coating composition according to the present invention comprises a lithium salt that has limited solubility in water.

[0028] The lithium salt has a solubility in water of at least 0.01, preferably 0.05, more preferably at least 0.1 g / L, measured in water at 20°C. Lithium salts with a solubility of at least 0.5, more preferably at least 1, even more preferably at least 5 g / L show particularly good results. Lithium salts with a solubility of less than 0.01 g / L do not show sufficient activity. The solubility of the lithium salt is less than 120 g / L, preferably less than 100 g / L, more preferably less than 85 g / L. Too high a solubility can lead to problems in the formulation of the coating composition, for example a non-uniform coating composition, which can lead to problems in application. The lithium salt has a solubility in the range of 0.01 to 120 g / L, measured in water at 20°C. The solubility is preferably in the range of 1 to 100 g / L. The solubility in water is measured according to OECD Guideline No. 105, EU method A.6 (flask method, procedure §23), which describes the preparation of a saturated solution, after which the concentration in the solution is measured by a suitable analytical method. Suitable analytical methods for determining the concentration of the relevant ions are known to the skilled person and can be selected depending on the ion. In particular, for lithium salts, the inductively coupled plasma mass spectrometry (ICP-OES) method is used.

[0029] The lithium salt is selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate. References herein to phosphates are references to orthophosphates unless otherwise indicated. The solubility of lithium carbonate in water is 13 g / L, lithium phosphate 0.39 g / L, lithium oxalate 62 g / L, and lithium tetraborate 28 g / L, all at 20° C. Preferably, the lithium salt is selected from the group consisting of lithium carbonate, lithium phosphate, lithium oxalate, and any mixture of two or more thereof. In some embodiments, lithium carbonate is the preferred salt. It can be used alone or in mixture with other lithium salts, such as lithium carbonate and lithium phosphate. In other embodiments, lithium phosphate may be preferred.

[0030] The coating composition preferably does not include lithium salts having a solubility of less than 0.01 g / L at 20° C. In another embodiment, the coating composition preferably does not include lithium salts having a solubility in water of more than 120 g / L at 20° C., such as lithium chloride or lithium nitrate. Preferably, the coating composition does not include any lithium salts other than lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate.

[0031] For best results, the lithium salt selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate is preferably present in the coating composition in an amount of at least 1.3 wt.%, more preferably at least 1.6 wt.%, even more preferably at least 2 wt.%, more preferably at least 2.5 wt.%, even more preferably at least 3 wt.% lithium based on the weight of the solids of the resin system. "Weight of solids of resin system" refers to the total dry weight of the resin system, i.e., all film-forming resins in the coating composition, and the hardener, if present. The amount of lithium salt selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate in the coating composition is such that the weight of lithium is preferably in the range of 1.3 to 40 wt.%, based on the weight of solids of the resin system. The coating composition preferably does not contain more than 40 wt.%, or more than 30 wt.%, or more than 25 wt.%, or more than 20 wt.%, or more than 15 wt.%, or more than 10 wt.% lithium based on the weight of solids of the resin system. Below 1.3 wt% lithium, the protective layer may not be sufficiently strengthened, especially when lithium carbonate is used as the lithium salt. At the upper limit, it may not be practical to include more lithium in the composition due to cost and because the effect is already achieved at low concentrations. When the lithium salt is lithium phosphate, the lithium phosphate is preferably present in an amount of at least 2.0 wt%, more preferably at least 3.0 wt%, even more preferably at least 4.0 wt%, and even more preferably at least 5.0 wt% lithium, based on the weight of the solids of the resin system.

[0032] The coating composition further comprises a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD).

[0033] The zinc salt of DMTD is 2,5-dimercapto-1,3,4 thiadiazole zinc salt (VII) (CAS 63813-27-4), which is a 1:2 salt of Zn and DMTD. The reference "1:2 salt" means herein that it is formed from 1 mole of Zn and 2 moles of DMTD. The salt is further referred to herein as Zn(DMTD)2 or "zinc salt of DMTD". The zinc salt of DMTD can be obtained by known methods, for example by reacting ZnO with DMTD as described in Example 1 of WO 02 / 092880. The zinc salt of DMTD is commercially available, for example as part of Inhibicor 1000 by WPC Technologies. The solubility of Zn(DMTD)2 in water is reported to be 0.4 g / L at 24°C.

[0034] In some embodiments, the zinc salt of DMTD is present in the coating composition in the absence of further zinc-containing compounds, such as zinc oxide and / or zinc salts, for example zinc orthophosphate or zinc cyanamide (CH2N2Zn). In particular, the coating composition does not contain any of ZnO, zinc orthophosphate, zinc cyanamide, or any combination thereof. In some embodiments, the coating composition does not contain ZnO. In some embodiments, the coating composition does not contain zinc orthophosphate. In yet other embodiments, the coating composition does not contain zinc cyanamide. In some embodiments, the composition does not contain ZnO, zinc orthophosphate, and zinc cyanamide. Without wishing to be bound by any theory, it is believed that Zn(DMTD)2 alone plays a role in enhancing the barrier properties of the protective layer formed by the lithium ions in the lithium salt, and therefore the presence of other Zn compounds is not necessary.

[0035] However, in other embodiments, it may be beneficial for the coating composition to include an additional zinc-containing compound, such as ZnO, zinc orthophosphate, zinc cyanamide, or any combination thereof. Examples of combinations are Zn(DMTD)2 and ZnO, or Zn(DMTD)2 and zinc orthophosphate, or Zn(DMTD)2 and zinc cyanamide. When Zn(DMTD)2 is present in combination with an additional zinc compound, the amount of Zn(DMTD)2 is 1-99% by weight, preferably 10-98% by weight, more preferably 20-95% by weight, and most preferably 30-90% by weight, based on the total weight of the zinc compounds.

[0036] In some embodiments, the content of Zn(DMTD)2 in the mixture with other zinc compounds can be 50% by weight, preferably more than 60% by weight, more preferably more than 70% by weight, most preferably more than 80% by weight, more preferably more than 90% by weight, based on the solids weight of the mixture. An example of a suitable mixture is 1-30% by weight of Zn orthophosphate, 1-20% by weight of ZnO, and at least 50% by weight, for example 50-98% by weight of Zn(DMTD)2, based on the solids weight of the mixture. A much lower content of Zn(DMTD)2 in the Zn compound mixture may result in insufficient protection, especially when the DMTD content in the coating composition is less than 0.05% by weight, based on the solids weight of the resin system.

[0037] In some embodiments, Zn(DTMD)2 is present in combination with other zinc compounds, such as ZnO, zinc orthophosphate, zinc cyanamide, or any combination thereof, and the amount of Zn(DTMD)2 in said mixture is greater than 50 wt.-%, preferably greater than 60 wt.-%, more preferably greater than 80 wt.-%, and most preferably greater than 90 wt.-%, based on the weight of the solids of the mixture, and the DMTD content in the coating composition is at least 0.05 wt.-%, preferably at least 1 wt.-%, and more preferably at least 2 wt.-%, based on the weight of the solids of the resin system.

[0038] Preferably, the zinc salt of DMTD is present in the coating composition to provide at least 0.05 wt% DMTD, more preferably at least 0.1 wt%, even more preferably at least 0.4 wt%, or at least 0.6 wt%, or at least 1 wt%, more preferably at least 2 wt% or at least 4 wt% DMTD based on the solids weight of the resin system. Preferably, the amount is less than 50 wt%, or less than 40 wt%, or less than 30 wt%, or less than 20 wt% DMTD based on the solids weight of the resin system. When used in an amount less than 0.05 wt%, the synergy with lithium is believed to be too low to actually provide any benefit. Using an amount greater than 50 wt% is believed to be impractical, for example, due to potential formulation problems or high cost.

[0039] The coating composition preferably contains the lithium salt and the zinc salt of DMTD in an amount such that the weight ratio of lithium to DMTD, calculated as the weight ratio of the lithium content to the DMTD content, is 0.01 to 20, preferably 0.1 to 10. In some embodiments, it may be preferred that the content of DMTD (present as the zinc salt of DMTD) is equal to or greater than the content of lithium (present as the lithium salt). In other embodiments, it may be preferred that the content of DMTD (present as the zinc salt of DMTD) is equal to or less than the content of lithium (present as the lithium salt).

[0040] According to the present invention, the zinc salt of DMTD is present as solid particles, the surface of which is at least partially covered by a layer of film-forming polymer. In this way, the zinc salt of DMTD is encapsulated by the polymer. Many polymers for encapsulation can be used, some of which are more suitable. For example, on the one hand, the polymer layer must shield the reinforcing agent (zinc salt of DMTD) from the coating components with which it may be reactive. At the same time, the activity of the reinforcing agent in the coating must be maintained after encapsulation. Without wishing to be bound by a particular theory, it is believed that this activity is based on the leaching of the lithium and zinc salts of DMTD from the coating onto the metal substrate at coating defects. Therefore, the encapsulating polymer matrix must allow the zinc salt of DMTD to leach out of the coating and exert its reinforcing effect, while simultaneously protecting the zinc salt from certain coating components.

[0041] The polymer layer may contain one or more film-forming polymers. The polymers may be organic or inorganic. The best results have been achieved with encapsulation based on melamine-formaldehyde, urea-formaldehyde and silica sol-gel. The most preferred film-forming polymer for encapsulation is melamine-formaldehyde.

[0042] The encapsulation of silica precursors into silica microcapsules by sol-gel reaction is generally known. This process involves the reaction of silanes with alkoxy orthosilicates in the presence of the compound to be encapsulated. Preferred silanes include epoxy-functional alkoxy silanes, such as Dynasilan Glymo, which is a bifunctional 3-glycidyloxypropyltrimethoxysilane from Evonik Industries. Suitable alkoxy orthosilicates are, for example, tetraethoxy orthosilicate (TEOS).

[0043] Melamine-formaldehyde encapsulation is carried out by polycondensation of melamine-formaldehyde monomers in the presence of the encapsulated compound. The condensation is brought about by lowering the pH and is preferably carried out in the presence of a surfactant. As surfactant any suitable, preferably polymeric surfactant is used. Preferably, poly(ethylene-alt-maleic anhydride) (polyEMA) is used. The surfactant can be used as a solution in a suitable solvent, for example water. The surfactant is preferably used in an amount of 0.01 to 20% by weight, more preferably 0.1 to 10% by weight, relative to the solid content of the metal salt of DMTD. Higher amounts of surfactant may require a washing step of the encapsulated material. As a result of the encapsulation the particles are at least partially covered with a layer of film-forming poly(melamine-formaldehyde).

[0044] If it is desired to reduce the free formaldehyde level in the encapsulating polymer, a formaldehyde scavenger can be used. A particularly preferred formaldehyde scavenger is ammonium chloride.

[0045] The solid particles covered by the polymer layer may also contain other Zn-containing compounds, such as Zn oxide and other Zn salts.

[0046] In some embodiments, the solid particles may include a zinc salt of DMTD as part of a hybrid compound, in which case it is preferably encapsulated as a whole. References herein to hybrid compounds (sometimes referred to as hybrid pigments) are inseparable intimate blends of two or more solid compounds, including both organic and inorganic compounds, typically formed by coprecipitation. Examples of hybrid compounds include host-guest compounds, where the host matrix is ​​inorganic and has a layered structure, and the guest compound is organic. However, in some embodiments, it is preferred that the zinc salt of DMTD does not form part of the hybrid pigment.

[0047] The inventors have discovered that the combination of a lithium salt in an organic coating with a zinc salt of DMTD shows an unexpected enhancement of the barrier properties of the protective layer formed on an exposed metal substrate. The protective layer is formed at locations where coating defects occur, which in the examples are simulated by a scribe that penetrates the coating and exposes the bare metal to the environment. Unlike other known corrosion inhibitors, lithium salts are known to form an irreversible protective layer on metal substrates (e.g., aluminum alloys) via a mechanism of leaching from the coating. The protective layer provides a barrier between the metal substrate and the environment. The barrier function of this layer is not visible to the naked eye, but can be measured using electrochemical impedance spectroscopy (EIS). The presence of Zn(DMTD)2 in the coating composition with the lithium salt and organic film-forming resin results in a much higher impedance value for the protective layer than when only the lithium salt is used or when the lithium salt is used with the other screened potentially active compounds. A higher impedance value means that the protective layer has a higher barrier function or is "enhanced". Here, a higher barrier function refers to a higher impedance modulus (Ωcm) for the same frequency range (Hz). 2 ), in particular a higher impedance modulus for frequencies of 10 Hz and 10 mHz as measured by EIS. The enhanced protective layer can provide improved or longer term protection. This enhancement of the protective layer is unexpected since Zn(DMTD)2 does not exhibit barrier properties or protective layer formation itself, as shown by the examples below.

[0048] Furthermore, it has been discovered by the present inventors and is demonstrated in the examples that the encapsulation of the zinc salt of DMTD in the film-forming polymer layer helps to extend the pot life of the coating composition, which would otherwise be short, and in some cases too short for practical use. Preferably, the pot life is in the range of 1 to 8 hours, more preferably 2 to 8 hours. A longer pot life is generally acceptable. Less than 30 minutes is generally unacceptable. At the same time, it is important that the activity of the zinc salt of DMTD as a toughening agent is preserved after encapsulation, as supported by the higher impedance values ​​in the EIS measurements in the examples.

[0049] The coating composition may further comprise at least one magnesium compound. Suitable magnesium compounds are magnesium-containing materials, such as magnesium metal, magnesium oxide, magnesium oxyaminophosphate salts (e.g., Pigmentan® 465M), magnesium carbonate, and magnesium hydroxide. Magnesium metal is preferably used in the form of particles, such as powder, flakes, spheres, or spheroids. It should be noted that magnesium metal and magnesium metal alloy particles require specific stabilizers when used in aqueous coating compositions. Such stabilizers are generally known and commercially available. Preferably, magnesium oxide is used as the magnesium compound.

[0050] The magnesium compound is preferably present in the coating composition in an amount of 0.1 to 50% by weight, more preferably 1 to 35% by weight, and most preferably 5 to 20% by weight, based on the dry weight of the coating composition (the sum of the weights of the non-volatile components of the coating composition).

[0051] The magnesium oxide or magnesium salt is preferably present in an amount such that the weight ratio of Mg:Li is at least 0.1:1, more preferably at least 0.5:1, even more preferably at least 1:1, and even more preferably at least 3:1. This ratio is preferably less than 30:1, more preferably less than 25:1, even more preferably less than 15:1, and even more preferably less than 10:1, and most preferably less than 8:1.

[0052] When magnesium metal or alloy is present in the composition according to the invention, the weight ratio Mg:Li is preferably less than 500:1, more preferably less than 300:1, even more preferably less than 250:1, even more preferably less than 100:1, even more preferably less than 50:1 and most preferably less than 25:1.

[0053] Preferably, the composition contains a combination of the lithium salt, magnesium oxide, and zinc salt of DMTD described above, preferably in a weight ratio of (1-5):(1-2):1, preferably about 3:1.5:1, for the lithium salt, magnesium oxide, and zinc salt of DMTD, respectively.

[0054] In some embodiments, the coating composition further comprises one or more additional corrosion inhibitors. The additional corrosion inhibitors can be organic or inorganic. Examples of inorganic inhibitors are phosphates, such as zinc orthophosphate, zinc orthophosphate hydrate, zinc aluminum orthophosphate; polyphosphates, such as strontium aluminum polyphosphate hydrate, zinc aluminum polyphosphate hydrate, magnesium aluminum polyphosphate, zinc aluminum triphosphate, and magnesium aluminum triphosphate. Inhibitors further include metal oxides, such as oxides of zinc, magnesium, aluminum, lithium, molybdate, strontium, cerium, and mixtures thereof: metals such as Zn metal, Mg metal, and Mg alloys. Examples of organic inhibitors are thiol compounds and azoles, such as imidazoles, thiazoles, tetrazoles, triazoles, such as (substituted) benzotriazoles, and 2-mercaptobenzothiazole.

[0055] In some embodiments, the additional corrosion inhibitor is a thiol compound other than 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII) or an azole. An azole is a five-membered N-heterocyclic compound that contains a nitrogen atom and at least one other non-carbon atom (i.e., nitrogen, sulfur, or oxygen) as part of the ring. Examples of suitable compounds include 5-methylbenzotriazole and 2-mercaptobenzothiazole (2-MBT). Preferably, 2-MBT is present as the additional corrosion inhibitor.

[0056] Other compounds which may be present in the coating composition according to the invention are colour pigments (e.g. titanium dioxide or yellow iron oxide), extenders (e.g. talcum, barium sulphate, mica, calcium carbonate, silica or wollastonite), rheology modifiers (e.g. Bentone SD 2 or organic rheology modifiers), flow and levelling agents (e.g. polysiloxane and polyacrylate levelling additives), and solvents (e.g. ketones such as methyl isobutyl ketone, aromatics such as xylene, alcohols such as benzyl alcohol, esters such as butyl acetate, and aliphatic solvents).

[0057] In a preferred embodiment, the coating composition according to the present invention is a liquid coating composition. The composition may contain a volatile liquid diluent, such as a volatile organic solvent or water. The composition may be water-based, solvent-based, or solvent-free. The term "solvent-free" is defined as containing a total content of volatile liquid diluent of less than 5% by weight, including water and organic solvent. The term "water-based" is defined as containing at least 50% by weight of water of the total weight of volatile liquid diluent (including both water and organic solvent). The coating composition is preferably solvent-based, which means that it contains organic solvent in an amount of at least 50% by weight, more preferably at least 80% by weight, even more preferably at least 95% by weight of the total weight of volatile liquid diluent (including both water and organic solvent).

[0058] In some embodiments, the coating composition is substantially free of water (non-aqueous), meaning that the water content is less than 1% by weight, preferably less than 0.1% by weight, based on the total weight of the coating composition. More preferably, the coating composition is free of water (non-aqueous), i.e., does not contain any water.

[0059] The coating composition according to the present invention is preferably a low temperature curable composition, meaning that it is curable, i.e. capable of forming a network, at temperatures below 120° C., preferably below 100° C., more preferably below 80° C., even more preferably below 50° C., and most preferably at ambient conditions (25° C.). In another embodiment, the coating composition is a high temperature curable composition, for example curable at temperatures of 120° C. or higher, preferably 140° C. or higher.

[0060] The non-volatile content of the coating composition is preferably 10 to 95% by weight, more preferably 25 to 75% by weight, and even more preferably 30 to 70% by weight.

[0061] The volatile organic content (VOC) of the coating composition (measured according to ASTM D3960) is preferably less than 700 g / L, such as less than 500 g / L, more preferably less than 300 g / L. The present invention is particularly advantageous when applied to high solids systems, e.g. non-aqueous solvent-based compositions with low VOC, such as less than 350 g / l.

[0062] The coating composition according to the present invention can be used as an anticorrosive primer for coating non-ferrous metal substrates, such as magnesium, magnesium alloy, titanium, aluminum, aluminum alloy, and lithium-aluminum alloy substrates.Preferred non-ferrous metal substrates are aluminum alloys.Examples of suitable aluminum alloys are 2024-T3 (bare or clad), 7075-T6 (bare or clad), 2098, 2099, 2198, 6061, 6111, 6022, 5052, 5083, 5251, 5454, 7475, 7017, and 7020.

[0063] The coating composition according to the invention is also suitable for coating iron substrates. Examples of suitable iron substrates are cold and hot rolled steel, stainless steel 304, B952 (zinc phosphate modified), B1000 (iron phosphate modified), and zinc modified steels such as EZG 60G, EZG 60G with zinc phosphate modification, G90, and Galvanneal HIA Zn / Fe A45.

[0064] The coating compositions according to the present invention can be used as primers, bonding primers, self-priming topcoats, intermediate coats and / or topcoats in coating systems in which at least two layers have the compositions described in this disclosure.

[0065] The coating compositions can be applied to substrates with or without the use of a hexavalent chromium-free pretreatment, such as a sol-gel system such as AC-® 131 (AC Tech), PreKote® (Pantheon Chemical), or a conversion treatment.

[0066] The coating composition may also be applied to anodized surfaces, such as chromate anodized (CAA) surfaces, tartaric acid sulfuric acid anodized (TSA) surfaces, sulfuric acid anodized (SAA) surfaces, phosphoric acid anodized (PAA) surfaces, phosphoric acid sulfuric acid anodized (PSA) surfaces, and borosulfuric acid anodized (BSAA) surfaces.

[0067] The coating composition can be advantageously used as a primer coating for non-ferrous metal substrates. It can be applied as a single layer or multiple layers. In a preferred embodiment, the coating composition is applied to the substrate to form at least one primer layer in a multi-layer coating system. The topcoat layer applied over the primer layer can be a clearcoat or a pigmented topcoat. Alternatively, the coating system can also include a color and / or effect-imparting basecoat applied over the primer layer and a clearcoat applied over the basecoat. The composition can also be used as a topcoat, the topcoat being either clear or pigmented.

[0068] The present invention also relates to a multi-layer coating system comprising at least one layer obtained from the coating composition according to the first aspect of the invention, i.e. comprising a resin system a), a lithium salt b) and a zinc salt c). After application, components a), b) and c) are present in a single layer. Preferably, the layer formed from the coating composition is used as a primer layer applied to a substrate, which is optionally pretreated. The topcoat may be a clearcoat or a pigmented topcoat, or the clearcoat is applied over the basecoat layer, if the topcoat comprises a color- and / or effect-imparting basecoat applied over the primer layer.

[0069] The present invention further provides a method of coating a metal substrate, the method comprising the steps of a) applying a coating composition according to the first aspect of the present invention to the metal substrate, and b) curing the applied coating composition. Any suitable method of coating application can be used, for example spraying, roller coating, etc. Curing can be carried out at ambient conditions (i.e. 25°C) or alternatively at elevated temperatures, for example 60-120°C. The skilled person will be aware of suitable conditions for curing the coating composition.

[0070] The present invention further provides a metal substrate coated with the coating composition according to the first aspect of the present invention. The metal substrate may be a non-ferrous metal substrate, such as aluminum or an aluminum alloy. Alternatively, the metal substrate may be a ferrous metal substrate. The substrate may be intended for external or internal use. Examples include aircraft structural parts, aircraft cabin parts or vehicles.

[0071] The coating compositions are particularly suitable for use in the aerospace, automotive or coil coating industries. EXAMPLES

[0072] Chemicals used ZnO - Zinc White Harzsiegel® from James M. Brown Ltd

[0073] 2,5-Dimercapto-1,3,4-thiadiazole from DMTD-Chemical Point Ltd.

[0074] PolyEMA - Poly(ethylene-alt-maleic anhydride) from Sigma-Aldrich, average molecular weight approximately 400,000

[0075] Cymel 350 - a highly methylated melamine resin consisting of a commercial version of hexamethoxymethylmelamine (HMMM) from Allnex

[0076] Epikote 828 - a medium viscosity liquid epoxy resin made from bisphenol A resin and epichlorohydrin from Hexion Europe BV

[0077] Solsperse 32500 - Polymeric dispersant in n-butyl acetate from Lubrizol Corp.

[0078] MPA 2000X - Rheological additive from Elementis

[0079] BYK 358 N - polyacrylate-based surface additive from BYK (member of the Altana Group)

[0080] Actiron NX3 - 2,4,6-tris(dimethylaminomethyl)phenol, a catalyst for epoxy coatings from Protex

[0081] Ancamine 2500 - an aliphatic amine-based hardener from Evonik Industries

[0082] Dynasylan N-2-aminoethyl-3-aminopropyltrimethoxysilane from DAMO-Evonik Industries

[0083] Dynasylan: Bifunctional 3-glycidyloxypropyltrimethoxysilane from Glymo-Evonik Industries

[0084] 1,4-Diazabicyclo[2.2.2]octane from DABCO-Evonik Industries

[0085] TEOS - Tetraethoxyorthosilicate from Sigma Aldrich, grade 98%

[0086] Lithium carbonate-ACS reagent, ≥99.0%, Sigma Aldrich

[0087] Lithium oxalate, lithium phosphate, MgO, NH4Cl - all from Sigma Aldrich

[0088] Desmophen 650 MPA - a branched hydroxyl-bearing polyester from Covestro AG, 65% by weight in 1-methoxypropyl acetate-2 (MPA), 5.3% OH content

[0089] Tioxide TR 92 - Titanium dioxide from Huntsman

[0090] Zn(DMTD)2 - prepared according to Example 1 of WO 02 / 092880 A1

[0091] Airwhite AW 15 - Barium Sulfate from Sibelco Specialty Minerals

[0092] Desmodur N-75 MPA / X-Aliphatic polyisocyanate resin based on hexamethylene diisocyanate (HDI), dissolved in n-butyl acetate and xylene (1:1) from Covestro AG, solids content 75% by weight, NCO content 16.5%

[0093] Silquest A-187 - an epoxy-functional silane from Momentive Performance Materials

[0094] Hybricor 204 - Zn(DMTD)2 containing pigment from WPC Technologies

[0095] Preparation of test panels Unless otherwise stated, the test panels were AA2024-T3 bare aluminum alloy, 7.0 cm by 7 cm (3 by 6 inches) and 0.8 mm thick, anodized in tartaric sulfuric acid (TSA) in accordance with aerospace requirements (AIPI 02-01-003).

[0096] The coatings were applied at ambient conditions (23°C, 55% RH) using a high volume, low pressure (HVLP) spray gun. After coating and a 1-hour flash-off period, the coated panels were cured at 80°C for 1 hour and dried under ambient conditions for 7 days. After drying, the coatings had a dry film thickness of 20-25 μm. The coated panels were scribed (cross scribe 2 cm x 2 cm) using a mechanical milling device to leave a U-shaped scribe (cross scribe 2 cm x 2 cm) with a width of 1 mm and a depth of 100-150 μm. After scribing, the samples were exposed to a neutral salt spray test (ASTM-B117) for 168 hours.

[0097] Electrochemical Impedance Spectroscopy (EIS) The barrier properties of the protective layer in the defect area were quantified and evaluated using electrochemical impedance spectroscopy (EIS) as described in Non-Patent Document 1: Visser, P., Liu, Y., Terryn, H. et al. “Lithium salts as leachable corrosion inhibitors and potential replacement for hexavalent chromium in organic coatings for the protection of aluminum alloys” J Coat Technol Res 13, 557-566 (2016)

[0098] EIS measurements were performed at open circuit potential (OCP) using a computer-controlled potentiostat over a frequency range of 0.01 Hz to 30,000 Hz, measuring seven points during a tenfold increase in frequency, applying a sinusoidal amplitude of 10 mV. Measurements were performed using a three-electrode configuration in a Faraday cage with a saturated calomel electrode (SCE) as the reference electrode, platinum gauze as the counter electrode, and a scribe panel as the working electrode, using 0.05 M NaCl electrolyte. The area exposed to the electrolyte was 12.5 cm. 2 and the effective bare electrode (i.e., coating defect) area is 0.48 cm 2 and the volume of the electrolyte is 60 cm 3 Measurements were recorded after 2 hours of exposure to 0.05 M NaCl electrolyte for at least three samples.

[0099] The results of the examples are presented in the form of a table with Zmod values ​​at 10 mHz and 10 Hz. The higher the impedance value, the stronger the protective layer.

[0100] Viscosity measurement The viscosity of the mixed coating composition was measured using an ISO-#4 flow cup according to the ISO 2431-19 standard method. In this method, the viscosity is measured in seconds until a cup with a defined opening is emptied. The sample was stirred while avoiding the formation of air bubbles. The orifice of the flow cup was closed with a finger and the cup was filled until the sample flowed over the rim. The excess paint was drained by sliding a glass plate over the rim. A container was placed under the flow cup. The time measurement started as soon as the finger was removed from the orifice. As soon as the first interruption of flow occurred near the orifice, the time measurement was stopped and the time of flow was recorded to the nearest 0.5 seconds. This was done up to 2 hours after the coating composition components were mixed.

[0101] Example 1 - Preparation of Zn(DMTD)2 The procedure from Example 1 of WO 02 / 092880 A1 was adapted to fit into a 2 liter three-neck flask. 62 g ZnO (0.76 mol) was mixed with 222 g demineralized water and heated at 60° C. for 1 hour in a 2 liter glass three-neck flask. At the same time, 222 g DMTD (1.48 mol) was mixed with 1480 g demineralized water. The DMTD / water mixture was added to the ZnO / water in 4 parts to prevent the temperature from dropping too much. After mixing everything, it was reacted at 60° C. for 2 hours. After the reaction was over, the stirrer was stopped and the material was allowed to cool. After decanting and increasing the solids content to more than 20%, the aggregate particle size was reduced by bead milling (using WAB's ECM Dynomill Multi Lab) using 0.5 mm ceramic beads. The slurry was passed through a mill until there were essentially no particles remaining with a size greater than 20 μm. The particle size was determined by laser diffraction (Malvern Mastersizer 2000). 90 The particle size was approximately 4 microns. The solids content was 16% by weight.

[0102] Example 2 - Preparation of MF modified Zn(DMTD)2 MF 11406 g of the slurry obtained in Example 1 was used for MF modification. 90 g of poly(ethylene-alt-maleic anhydride) (polyEMA, average molecular weight about 400,000) powder was mixed with 1410 ml of demineralized water, shaken for 3 days, and then allowed to settle. 375 grams of the mixture was mixed with 1.7 g of NH4Cl for 1 hour. This is equivalent to 22.5 g of polyEMA, which is 10% on solid Zn(DMTD)2. The Zn(DMTD)2 slurry and the EMA / water / NH4Cl mixture were added to a 2000 ml three-neck flask and heated to 55°C. The pH of the emulsion was measured to be 3.0 at 55°C. To this system was added a solution of 45 g of Cymel 350 (20% on solid Zn(DMTD)2) with 55 g of demineralized water. The pH of the slurry is adjusted to 2.3 with 10 (v / v)% H2SO4 at 55 °C. After 3.33 h, the heat is turned off and the mixture is stirred overnight without heat. The next morning, stirring is stopped. After one centrifugation and drying, the dried material is collected.

[0103] The product was washed to remove surfactant according to the following method: The material was centrifuged in a Heraeus Varifuge F at 2500 / 3000 rpm for 10 minutes, after which the upper phase was removed. Water was added, the material homogenized, and centrifuged again. This was repeated until the material had been centrifuged four times. Water was removed and the material was dried in a vacuum oven. The material was then ground with a pestle and mortar.

[0104] MF2 and MF3 : The above method was repeated by using different amounts of surfactants PolyEMA and Cymel 350. Also, the material was not washed because the amount of surfactant was low and did not adversely affect the viscosity test. The differences between procedures MF mod 1, mod 2, and mod 3 are summarized in Table 1 below.

[0105] [Table 1]

[0106] Example 3 - Coating Composition Formulations 1-1 to 1-3 were prepared using the components listed in Table 2. The component contents are given in parts by weight (g). The formulations were prepared according to the method described above. The formulations have 30% PVC and 350 g / L VOC.

[0107] [Table 2]

[0108] Formulations 1-1 and 1-2 are comparative formulations and formulation 1-3 is in accordance with the invention.

[0109] The pot life of the coating composition was evaluated by measuring the change in flow cup viscosity over time, and the results are shown in Figure 1.

[0110] It can be seen that the samples containing unmodified Zn(DMTD)2 initially develop a high viscosity, probably due to the reaction of Zn(DTMD)2 with the coating components. However, when Zn(DTMD)2 is encapsulated in a melamine-formaldehyde polymer layer, the viscosity is low and comparable to that of the samples without Zn(DMTD)2.

[0111] Formulations 1-1 through 1-3 were applied to Al 2024 T3 panels as described in Panel Preparation and subjected to testing as described in Methods Used. The results of the EIS measurements are listed in Table 3.

[0112] [Table 3]

[0113] The results in Table 3 show that the synergistic effect between Li salt and Zn(DMTD)2 is preserved when Zn(DMTD)2 is encapsulated.

[0114] Example 4 - Encapsulation with alternative polymers Silane Encapsulation Zn(DMTD)2 containing pigment (formerly Hybricor 204 from WPC Technologies) was encapsulated with silane according to the following process: 75g of Hybricor 204 was added to 87g of methyl amyl ketone. After this, 0.83g of Dynasylan Glymo and 0.015g of DABCO were added to the mixture. The mixture was heated to 40°C under stirring for 3 hours, after which 21g of tetraethoxyorthosilicate (TEOS) was added along with 0.4g of NaOH 0.1M. The mixture was stirred at 40°C for 6 hours using a glass stirrer to obtain silane encapsulated Zn(DMTD)2 containing pigment (55% solids in MEK).

[0115] Acrylic polymer encapsulation The encapsulation of Zn(DMTD)2 with acrylic polymer was performed according to a proprietary method similar to that described in Example 1 of EP 0 477 433. For sample "acrylic modified 1", 11.5 wt. % polyacrylate polymer was used relative to the Zn(DMTD)2 solids, and for sample "acrylic modified 2", 9.7 wt. % polyacrylate polymer was used relative to the Zn(DMTD)2 solids.

[0116] Coating compositions were prepared in the same manner as Formulations 1-3 in Example 3, except that different encapsulated pigments were used in place of MF 1. The viscosity of the coating compositions after mixing was followed over time as described above.

[0117] The results of the viscosity measurements are shown in FIG.

[0118] It can be concluded that encapsulation with melamine-formaldehyde (MF) and silane provides the best encapsulation.

[0119] The synergistic effect between the lithium and zinc salts of DMTD is further demonstrated in Comparative Examples 1-7, all of which are comparative examples since a non-encapsulated version of the zinc salt of DMTD was used.

[0120] Comparative Example 1 - Synergistic effect of Li salt and Zn(DTMD)2 Formulations C1-1 to C1-4 were prepared using the components listed in Table 4. The component contents are given in parts by weight (g), and the contents of the active components Li and DMTD are given as weight % based on the resin system solids.

[0121] The ingredients of Component A were added sequentially to a 370 ml glass jar with stirring. Then, 400 grams of Zirconox pearls (1.7-2.4 mm) were added to the mixture for grinding and dispersion of the pigment. The sample was shaken for 20 minutes in a Skandex paint shaker to achieve a grinding degree of less than 25 μm. After shaking, the pearls were separated from the coating. Component B was prepared separately by mixing.

[0122] Component B was added to Component A under stirring to ensure sufficient mixing to obtain a homogenous sample. After mixing of the separate components, the coating was allowed to induce for 30 minutes.

[0123] The results of the EIS measurements are listed in Table 4.

[0124] [Table 4]

[0125] It can be seen that the coatings containing both Zn(DMTD)2 and Li salt (C1-4) show significantly higher impedance |Z| (also called "Zmod") values ​​than the formulations without active ingredient (C1-1), or the formulations containing only Zn(DMTD)2 (C1-2) or only Li salt (C1-3). This effect is much stronger than the sum of the individual effects of the Li salt (C1-3) and Zn(DMTD)2 (C1-2), and is therefore a synergistic effect.

[0126] The results also show that Zn(DMTD)2 alone (C1-2) does not affect the formation of a protective layer in the defect area. In particular, the coating C1-2 has a low impedance value comparable to that of no coating (negative reference) (C1-1).

[0127] Comparative Example 2: Comparison with other azoles Formulations C2-1 to C2-7 were prepared in the same manner as Comparative Example 1, but with the ingredients as shown in Table 5. The ingredient contents are given in parts by weight (g). The active ingredient contents are also given in weight % based on the resin system solids. The molar amount of the azole is the same across all formulations in this example. BTA is benzotriazole and 2-MBT is 2-mercaptobenzothiazole. The results of the EIS measurements are listed in Table 5.

[0128] [Table 5]

[0129] The results show that the combination of Li salts with other azoles (BTA or 2-MBT) does not have the same synergistic effect as the combination with Zn(DMTD)2. The combination of Li salts with Zn(DMTD)2 provides much higher impedance values ​​associated with strengthening of the protective layer in the defect areas, indicating a better strengthening of the protective layer in the defect areas.

[0130] Comparative Example 3 - Li salts of different concentrations Formulations C3-1 to C3-8 were prepared in the same manner as Comparative Example 1, but with ingredients as listed in Table 6. The ingredient contents are listed in parts by weight (g). The amount of active ingredient is also listed as weight % based on the resin system solids. The results of EIS measurements are also listed in Table 6. In these experiments, the formulations contained Li salt and Zn(DTMD)2 with various concentrations of Li salt.

[0131] [Table 6]

[0132] It can be seen that significantly higher impedance values ​​are obtained for compositions containing at least 1.3 wt. % Li relative to the resin system solids in combination with Zn(DMTD)2 compared to samples containing only Li salts.

[0133] Comparative Example 4 - Different Concentrations of Zn(DMTD)2 Formulations C4-1 to C4-8 were prepared in the same manner as Comparative Example 1, but with ingredients as listed in Table 7. The ingredient contents are listed in parts by weight (g). The amount of active ingredient is also listed as weight % based on the resin system solids. The results of EIS measurements are also listed in Table 7. In these experiments, the active materials included Li salt and Zn(DTMD)2 with various concentrations of Zn(DTMD)2.

[0134] [Table 7]

[0135] It can be concluded that Zn(DTMD)2 shows a synergistic effect with any amount of Li salt, even at very small amounts of DMTD, such as 0.6 wt.%, that even at these low concentrations of DMTD there is a clear improvement (strengthening effect) of the barrier properties of the protective layer in the defect areas.

[0136] Comparative Example 5 - Different Li Salts (4.4% Li) Formulations C5-1 to C5-8 were prepared in the same manner as Comparative Example 1, but with ingredients as listed in Table 8. The content of ingredients is given in parts by weight (g). The amount of active ingredient is also given in weight % based on the resin system solids. The results of EIS measurements are also listed in Table 8. In these experiments, the coatings contain different soluble Li salts, with the Li content being 4.4 wt % based on the resin system solids. The lithium salts are selected with different solubilities.

[0137] [Table 8]

[0138] It can be concluded that Zn(DTMD)2 shows a reinforcing effect with Li salts whatever the salt used. The moderate effect on lithium phosphate is likely due to its low solubility in water.

[0139] Comparative Example 6 - Different Li Salts (1.3 wt% Li) Formulations C6-1 to C6-6 were prepared in the same manner as Comparative Example 1, but with ingredients as listed in Table 9. The content of ingredients is given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids. The results of EIS measurements are also listed in Table 9. In these experiments, the coatings contained different soluble Li salts, and the Li content was 1.3 wt % based on the resin system solids.

[0140] [Table 9]

[0141] It can be concluded that Zn(DTMD)2 shows enhanced protective layers for most Li salts, even when used in amounts less than Comparative Example 5, except for lithium phosphate, for which better results were achieved with higher Li content (Comparative Example 5), which is likely due to its lower solubility in water.

[0142] Comparative Example 7 - No Magnesium Oxide Formulations C7-1 to C7-4 were prepared in the same manner as Comparative Example 1, but with ingredients as shown in Table 10. The content of ingredients is given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids. The results of the EIS measurements are listed in Table 10. These experiments test whether the reinforcing effect is also present in compositions that do not contain magnesium oxide.

[0143] [Table 10]

[0144] It can be concluded that the strengthening effect exists even in the absence of MgO and is purely due to the combination of the lithium salt with Zn(DMTD)2.

[0145] Comparative Example 8 - Lithium phosphate of different concentrations Formulations C8-1 to C8-6 were prepared in the same manner as Comparative Example 1, but with the ingredients as shown in Table 11. The ingredient contents are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0146] In these experiments, the concentration of lithium phosphate is varied so that the Li content of the resin-based solids is 2.0 to 7.0 wt.

[0147] [Table 11]

[0148] Test panels were prepared and scribed as described above. After scribing, the samples were exposed to a neutral salt spray test (ASTM-B117) for 96 hours. The results of the EIS measurements are listed in Table 11. The present invention includes the following aspects. Section 1. a) a resin system comprising an organic film-forming resin and optionally a curing agent reactive with said organic film-forming resin; b) a lithium salt having a solubility in water in the range of 0.01 to 120 g / L at 20° C. selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate; c) a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), wherein the zinc salt of DMTD is 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII); Including, the zinc salt of DMTD is present as solid particles, the surface of which is at least partially covered by a layer of a film-forming polymer; Coating composition. Section 2. Item 2. The composition according to item 1, wherein the organic film-forming resin is an epoxy resin. Section 3. Item 3. The composition according to item 1 or 2, wherein the resin system comprises a curing agent, and the curing agent is selected from the group consisting of aliphatic or aromatic amines, polyamides and thiols. Section 4. Item 4. The composition according to item 3, wherein the hardener comprises a melamine resin. Section 5. Item 5. The composition according to any one of items 1 to 4, wherein the film-forming polymer is a melamine-formaldehyde polymer. Section 6. Item 6. The composition of any one of items 1 to 5, wherein the lithium salt is present in an amount of at least 1.3 wt.% lithium based on resin system solids. Section 7. Item 7. The composition according to any one of items 1 to 6, wherein the lithium salt is selected from the group consisting of lithium carbonate, lithium bicarbonate, lithium tetraborate, and lithium oxalate, preferably lithium carbonate and lithium oxalate, more preferably lithium carbonate. Section 8. Item 7. The composition according to any one of items 1 to 6, wherein the lithium salt is lithium phosphate, and the lithium phosphate is present in an amount of at least 2.0 wt.%, preferably at least 3.0 wt.%, more preferably at least 4.0 wt.%, lithium, based on the weight of the solids of the resin system. Section 9. Item 9. The composition according to any one of items 1 to 8, wherein the zinc salt of DMTD is present in an amount of 0.05 to 50% by weight of DMTD based on the solids weight of the resin system. Section 10. Item 10. The composition according to any one of items 1 to 9, which is a solvent-based composition. Section 11. Item 11. A multi-layer coating system on a metal substrate comprising a layer obtained from the coating composition according to any one of items 1 to 10. Section 12. Item 12. The multi-layer coating system according to item 11, wherein the layer obtained from the coating composition according to any one of items 1 to 10 is a primer layer on the metal substrate. Section 13. 1. A method for coating a metal substrate, comprising: a) applying the coating composition according to any one of items 1 to 10 to the metal substrate; b) curing the applied coating composition; A method comprising: Section 14. Item 11. A metal substrate coated with the coating composition according to any one of items 1 to 10.

Claims

1. a) a resin system comprising an organic film-forming resin and optionally a curing agent reactive with said organic film-forming resin; b) a lithium salt having a solubility in water ranging from 0.01 to 120 g / L at 20° C. selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate; c) a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), wherein the zinc salt of DMTD is 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII); Including, The zinc salt of DMTD is present as solid particles, the surface of which is at least partially covered by a layer of a film-forming polymer. Coating composition.

2. The composition of claim 1 wherein the organic film-forming resin is an epoxy resin.

3. The composition of claim 1 , wherein the resin system comprises a curing agent, the curing agent being selected from the group consisting of aliphatic or aromatic amines, polyamides and thiols.

4. The composition of claim 3 , wherein the hardener comprises a melamine resin.

5. The composition of claim 1, wherein the film-forming polymer is a melamine-formaldehyde polymer.

6. 10. The composition of claim 1, wherein the lithium salt is present in an amount of at least 1.3% by weight lithium based on resin system solids.

7. 2. The composition of claim 1, wherein the lithium salt is selected from the group consisting of lithium carbonate, lithium bicarbonate, lithium tetraborate, and lithium oxalate.

8. 2. The composition of claim 1, wherein the lithium salt is lithium phosphate, and the lithium phosphate is present in an amount of at least 2.0% lithium by weight, based on the weight of solids of the resin system.

9. 10. The composition of claim 1, wherein the zinc salt of DMTD is present in an amount of 0.05 to 50 weight percent DMTD based on the weight of solids of the resin system.

10. The composition of claim 1 which is a solvent-based composition.

11. A multi-layer coating system on a metal substrate comprising a layer obtained from a coating composition according to any one of claims 1 to 10.

12. 12. The multi-layer coating system of claim 11, wherein the layer obtained from the coating composition of any one of claims 1 to 10 is a primer layer on the metal substrate.

13. 1. A method for coating a metal substrate, comprising: a) applying a coating composition according to any one of claims 1 to 10 to the metal substrate; b) curing the applied coating composition; A method comprising:

14. A metal substrate coated with the coating composition of any one of claims 1 to 10.

Citation Information

Patent Citations

  • Multilayer and complex corrosion-resistant coating

    JP2010520096A

  • Corrosion resistant adhesive sol-gel

    JP2018154813A

  • Curable film-forming composition containing lithium silicate as a corrosion inhibitor and a metal substrate coated with multiple layers

    JP2018524421A

  • Hybrid pigment grade corrosion inhibitor compositions and procedures

    WO1999018044A1

  • Anti-corrosive coating composition

    WO2010112605A1